Confinement of the Permittivity Enhancing Fillers in Bacterial Cellulose for Dielectric Elastomer Applications - Nur Syafiqah, Ismail; Syed Muhammad Aiman, Syed Mohd Hakhiri; Siti Noor Hidayah, Mustapha; Aliff Hisyam, A Razak; Mohd Hairul, Ab. Rahim; Shamsul, Zakaria (Trans Tech Publications, Switzerland, 2024)
The electromechanical performances of dielectric elastomers were investigated after the incorporation of the confined permittivity enhancing fillers in bacteria cellulose (BC) into polydimethylsiloxane (PDMS) films. The purpose of this study is to investigate the capability of BC as a confinement matrix for the permittivity enhancing fillers to overcome the low relative permittivity and at the same time to increase the softness of the PDMS films. The metal oxide and silicone oil were confined in BC before being physically mixed with PDMS at different percentages. The results showed that the confined TiO2-BC increased the relative permittivity and at the same time maintained the softness of the PDMS films to some extent. In addition to that, by adding confined silicone oil-BC into the PDMS films, this PDMS based dielectric elastomer (DE) becomes even softer.